Sistem Penunjang Keputusan Penerima Bantuan Rumah Tidak Layak Huni (RTLH) Menggunakan Metode Swara - Ardiansyah, Maulana; Fahmi, Hairul; Imtihan, Khairul (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The Rumah Tidak Layak Huni (RTLH) Assistance Program is a government initiative aimed at improving the quality of life of low-income communities through the renovation of houses that do not meet livability standards. However, the selection process for beneficiaries still faces several challenges, particularly the lack of objectivity, potential subjectivity of field officers, and limitations in accurate assessment methods. This study aims to develop a Decision Support System (DSS) using the Step-wise Weight Assessment Ratio Analysis (SWARA) method to determine the weight of criteria in a structured manner based on expert judgment. SWARA was chosen because it systematically accommodates expert preferences through simple steps, producing more consistent and transparent weighting compared to other approaches.Five main criteria were considered: family income (C1), number of dependents (C2), physical condition of the house (C3), ownership status (C4), and occupation of the head of household (C5). The SWARA results generated the following weights: C1 = 0.288, C2 = 0.240, C3 = 0.185, C4 = 0.168, and C5 = 0.120. Data were collected from 13 respondents using a 1–4 scale questionnaire. Final scores were calculated by multiplying responses with the respective weights, yielding a maximum score of 3.160 and a minimum of 2.160. Using quantile-based classification, four eligibility categories were determined: Not Eligible, Less Eligible, Eligible, and Highly Eligible.The results showed that 3 respondents were classified as Not Eligible, 4 as Less Eligible, 3 as Eligible, and 3 as Highly Eligible. This study demonstrates that SWARA can be effectively applied in DSS to enhance the accuracy, objectivity, and transparency of RTLH beneficiary selection.